The protective effect of Centella asiatica and its constituent, araliadiol on neuronal cell damage and cognitive impairment - Honoka Fujimori; Takuya Ohba; Masashi Mikami; Shinsuke Nakamura; Kenichi Ito; Hiroyuki Kojima; Tatsuji Takahashi; Arunasiri Iddamalgoda; Masamitsu Shimazawa; Hideaki Hara (Elsevier, 2022)
Alzheimer's disease (AD) is characterized by progressive cognitive decline, and the number of affected individuals has increased worldwide. However, there are no effective treatments for AD. Therefore, it is important to prevent the onset of dementia. Oxidative stress and endoplasmic reticulum (ER) stress are increased in the brains of AD patients, and are postulated to induce neuronal cell death and cognitive dysfunction. In this study, Centella asiatica, a traditional Indian medicinal herb, were fractionated and compared for their protective effects against glutamate and tunicamycin damage. Araliadiol was identified as a component from the fraction with the highest activity. Further, murine hippocampal cells (HT22) were damaged by glutamate, an oxidative stress inducer. C. asiatica and araliadiol suppressed cell death and reactive oxygen species production. HT22 cells were also injured by tunicamycin, an ER stress inducer. C. asiatica and araliadiol prevented cell death by mainly inhibiting PERK phosphorylation; additionally, C. asiatica also suppressed the expression levels of GRP94 and BiP. In Y-maze test, oral administration of araliadiol (10 mg/kg/day) for 7 days ameliorated the arm alternation ratio in mice with scopolamine-induced cognitive impairment. These results suggest that C. asiatica and its active component, araliadiol, have neuroprotective effects, which may prevent cognitive dysfunction.